Philosophy-in-action in university teaching - Sue M. Scott; Donna M. Chovanec; Beth Young (Adult Education Research Conference, 1993)
Eleven professors expressed traditional, humanist, and critical philosophies as they dialogued on the relationship between their philosophy of teaching and their practice in the classroom. Four categories emerged using grounded theory, axial coding methods.